The poverty and distributional impact of macroeconomic shocks and policies : a review of modeling approaches - Essama-Nssah, Boniface, 1949- 1949- (Policy research working paper, 2005)
"The importance of distributional issues in policymaking creates a need for empirical tools to assess the social impact of economic shocks and policies. This paper reviews some of the modeling approaches that are currently in use at the World Bank and other international financial institutions. The specification of these models is dictated by the issues at stake, the knowledge about the nature of the process involved, and the availability and reliability of relevant data. Furthermore, shocks and policies have macroeconomic, structural, and distributional implications. This creates interdependence between such policy issues. Finally, the distributional impact of shocks and policies hinges on the heterogeneity of socioeconomic agents with respect to endowments and behavior. In the end, each modeling approach should be judged on how well it handles the interdependence between policy issues and the heterogeneity of the stakeholders, given other constraints. "--World Bank web site